Analisis Patron Klien Terhadap Kemenangan Partai Golkar Kabupaten Tanah Datar Sejak Reformasi - Irvan Ansyari; Priyatno Harsasto; Fitriyah Fitriyah (Indonesian Journal of Religion and Society, 2019)
Golkar as the dominance party in Tanah Datar is an interesting case study for Islamic values area in their customs. This shows the weak political flow in Tanah Datar. The political dominance of Golkar has occurred since the New Order era until the collapse of the new order power that showed by the winner of regional head elections (Bupati), Golkar in DPRD and the power of the Golkar Party. This study used qualitative descriptive through in-depth interviews with selected informants through purposive sampling. The results indicate that the patron client relationship occurs between the Golkar Party cadres and the supporting community. This is indicated by a very wide and structured Golkar Party network starting from the Regent, adat institutions, religious leaders, businessmen, cultural figures and Wali Nagari.